Carbonisation Of Dead Leaves Biomass As Activated Carbon For Potential Application As Reinforcement Filler In Natural Rubber Composites - Zulkifli, Aiman (Universiti Sains Malaysia, 2018)
This project studies the effect of the dead leaves biomass as activated carbon (DLAC) for potential application as reinforcement filler in SMRL rubber. The DLAC was produced from dead leaves biomass by pyrolysis technique using nitrogen gas as the activation medium at different temperatures (550, 700, 900 and 1000 °C). The dead leaves activated carbon were prepared by heating at a heating rate 20 °C/min to the final carbonization temperature. The activated carbon were characterized by particle size analysis, FESEM, EDX, Raman Spectroscopy and density and compared with carbon black. EDX showed that the dead leaves activated carbon produced at 1000 °C have high carbon content with low oxygen content compared to other carbonization temperatures. DLAC at 1000 °C was then used as filler in SMRL rubber vulcanizate and the properties were compared with carbon black filler. The filler loading was variedat 0, 5, 10 and 15 phr. The two roll mill was used to produce the rubber compound. Curing, mechanical and thermal properties were investigated to assess the effectiveness of the dead leaves activated carbon as reinforcement filler for rubber matrix. The curing characteristics become faster, the tensile strength, modulus 100%, modulus 300% and hardness were found to decrease and elongation at break increased about 12% with increasing the dead leaves activated carbon content. The thermal stability of rubber compound filled dead leaves activated carbon was low. Morphological studies using SEM revealed that the dispersion of activated carbon in natural rubber was poor. However, interaction between filler and rubber matrix increased as the activated carbon content increased.